2019
DOI: 10.1111/ajr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Young bisexual women's sexual health care experiences in Australian rural general practice

Abstract: Objective: To examine how young bisexual women in rural Tasmania experience routine sexual health care in general practice settings. Design: Semi-structured interviews with bisexual women were used for this study.Self-selected and purposive sampling were used to recruit women in 2015. Participants were recruited via community social media pages and a not-for-profit organisation supporting same-sex attracted rural youth. Data were analysed thematically. Setting: Regional and rural areas in the north and south o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…People living in regional, rural, and remote areas (referred to as rural people herein) have poorer access to healthcare than their metropolitan counterparts, and experience higher rates of illness, injury, disability and early death, even in high income countries such as Australia (Australian Institute of Health and Welfare 2019). Rural people travel further than their metropolitan counterparts to access care, and often receive care later than required, in an inconsistent and inappropriate manner, or not at all (Australian Institute of Health and Welfare 2019; McBain-Rigg and Veitch 2011;Grant and Nash 2019;O'Callaghan et al 2005). Lacking services in rural settings perpetuate the normalisation of self-reliant behaviours, and at times delay health seeking behaviours until emergency care is required (Page-Carruth et al 2014).…”
Section: Access To Healthcare In Rural Areasmentioning
confidence: 99%
“…People living in regional, rural, and remote areas (referred to as rural people herein) have poorer access to healthcare than their metropolitan counterparts, and experience higher rates of illness, injury, disability and early death, even in high income countries such as Australia (Australian Institute of Health and Welfare 2019). Rural people travel further than their metropolitan counterparts to access care, and often receive care later than required, in an inconsistent and inappropriate manner, or not at all (Australian Institute of Health and Welfare 2019; McBain-Rigg and Veitch 2011;Grant and Nash 2019;O'Callaghan et al 2005). Lacking services in rural settings perpetuate the normalisation of self-reliant behaviours, and at times delay health seeking behaviours until emergency care is required (Page-Carruth et al 2014).…”
Section: Access To Healthcare In Rural Areasmentioning
confidence: 99%
“…The language and tone of the provider were also found to be essential with those appearing to judge an individual's sexual practice or make stereotypical sex-based assumptions found to be less-sensitive. 31 Self-reflection on one's practice might therefore be required to ensure culturally and socially inclusive care is provided. 32 Makadon 12 notes the importance of a welcoming environment to create trust and comfort in the health care experience.…”
Section: The Health Systemmentioning
confidence: 99%
“…This results in a lower level of trust in the health service provider and reduced comfort when discussing health care needs. The language and tone of the provider were also found to be essential with those appearing to judge an individual's sexual practice or make stereotypical sex‐based assumptions found to be less‐sensitive 31 . Self‐reflection on one's practice might therefore be required to ensure culturally and socially inclusive care is provided 32 …”
Section: Implications For Rural Service Provisionmentioning
confidence: 99%
“…We use the term ‘LGBTI + inclusive healthcare’ in this article, although cultural competence is frequently used in the US and Canadian literature. Numerous studies have concluded that LGBTI + inclusive healthcare is important in delivering optimised healthcare, including alcohol treatment and mental health (McNair et al., 2018), HIV prevention, including pre‐exposure prophylaxis (Maloney et al., 2017; Smith, Holt, Hughes, Truong, & Newman, 2019), sexual and reproductive health (Grant & Nash, 2019; Logie et al., 2019; Malmquist & Nelson, 2014), cancer treatment (Quinn et al., 2015), dementia care (Price, 2010) and aged care (Waling et al., 2019). Access to and provision of high‐quality healthcare, free from discrimination, pertaining to diverse sexual orientation, gender identity, gender expression and sex characteristics is an explicit right in the Yogyakarta Principles plus 10, the highest level international human rights instrument pertaining to LGBTI + people (Yogyakarta Principles plus10, 2017; Zeeman et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this unique health profile, as the last Australian state to decriminalise homosexuality in 1997, Tasmania has a particular LGBTI + social history that arguably shapes contemporary LGBTI + health and well‐being. While there is limited research examining LGBTI + health in the state of Tasmania, previous studies highlight barriers to inclusive services (Grant & Nash, 2019; Grant et al., 2020). For this reason, Tasmania is a compelling site to examine healthcare students' and clinicians' understandings and approaches to LGBTI + inclusive practice.…”
Section: Introductionmentioning
confidence: 99%